11-(9x)+2x-(-9)=

Simple and best practice solution for 11-(9x)+2x-(-9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11-(9x)+2x-(-9)= equation:


Simplifying
11 + -1(9x) + 2x + -1(-9) = 0

Remove parenthesis around (9x)
11 + -1 * 9x + 2x + -1(-9) = 0

Multiply -1 * 9
11 + -9x + 2x + -1(-9) = 0

Multiply -1 * -9
11 + -9x + 2x + 9 = 0

Reorder the terms:
11 + 9 + -9x + 2x = 0

Combine like terms: 11 + 9 = 20
20 + -9x + 2x = 0

Combine like terms: -9x + 2x = -7x
20 + -7x = 0

Solving
20 + -7x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-20' to each side of the equation.
20 + -20 + -7x = 0 + -20

Combine like terms: 20 + -20 = 0
0 + -7x = 0 + -20
-7x = 0 + -20

Combine like terms: 0 + -20 = -20
-7x = -20

Divide each side by '-7'.
x = 2.857142857

Simplifying
x = 2.857142857

See similar equations:

| r=d/1-t | | (-t/2)=12 | | 7*z*0=0 | | -11=4a-3 | | -8(1-7n)+7(n+3)= | | 5n-3n+7+2n= | | 24a+72b-40c= | | 13*0*p=0 | | 6j-4j+12=6j-3j+30 | | 42-48v=-54 | | 9=8-x/4 | | 4(2a)-a= | | 4w-5=12w-4 | | (4x^2-1)(6x^2-9)= | | 5(d+5)+2d=-13-8d | | 1/3x-8=4/9x | | 20=a/9 | | 26=13/v | | -7(3a-2)+4(5a+5)= | | 10=6+(1+3m)-2(2+10m) | | X-y=110 | | 7x-3x(x+1)= | | 6+2[3j-2]=4[1+j] | | 1/y-1/2=4 | | 6(z/2-5)=36 | | q=10000-125p | | 12x^2-121/12=0 | | 12=m/5 | | X+y=280 | | 5.5=-1.5+x | | 2.3+n+1.4=0 | | x-86=135 |

Equations solver categories